The synergetic effect of reducing pollutants and carbon quantified by exergy flow integrated resources and energy in an iron and steel symbiosis network. (15th March 2022) - Wu, Junnian; Lu, Jiayi
Abstract: That the synergy of pollutants and carbon emission impact on the co-operated utilization of resources and energy can regulate the symbiosis network. Ecological Network Analysis (ENA) of exergy flow has been proposed to quantify the synergetic effects on the iron and steel industry symbiosis network (ISISN) in this study. Waste Management that represents all disposing discharge of wastes should take measures about emission reduction which has the highest emission pollutants and carbon (9634 kJ exergy loss/kg crude steel and 1.28 kg CO2 /kg crude steel). External Environment that represents the supplier of resources and energy and receiver of products and pollutants has the highest synergy of resources and energy metabolism as it reaches 32.7% of trophic constitution in the ISISN, which needs to improve the resources and energy utilization efficiency. The results of ENA show that the relationship of exploitation dominates the network, which occupied 49.1% of all the relationships among components. And External Environment is the biggest direct utility contributor and it is also the biggest indirect utility receiver. Ore-dress is the biggest direct utility receiver and Sintering is the biggest indirect utility contributor. Control degree achieve 32.7% in External Environment component but only 0.4% in Pellets component. The methodology in this study identifies key components in reduction of pollutant and carbon emission and quantifies synergetic effects of exergy loss and exergy efficiency in the ISISN. Our findings may be helpful to assess and manage synergetic effect as well as low-carbon transformation and development in the industrial symbiosis network. Highlights: Using ecological network analysis of exergy flow to quantify the synergetic effects. Synergy of pollutants and carbon emission were characterized by exergy loss. Synergy of resources and energy metabolisms were characterized by exergy flow. External Environment and Waste Management were the key components in the ISISN. The synergetic effects are significantly influenced by indirect interaction among components.